The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsnano.0c08842
|View full text |Cite
|
Sign up to set email alerts
|

Strain Relaxation in “2D/2D and 2D/3D Systems”: Highly Textured Mica/Bi2Te3, Sb2Te3/Bi2Te3, and Bi2Te3/GeTe Heterostructures

Abstract: Strain engineering as a method to control functional properties has seen in the last decades a surge of interest. Heterostructures comprising 2D-materials and containing van der Waals(-like) gaps were considered unsuitable for strain engineering. However, recent work on heterostructures based on Bi 2 Te 3 , Sb 2 Te 3 , and GeTe showed the potential of a different type of strain engineering due to long-range mutual strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The corresponding targets were obtained from KTECH with a purity of 99.999%. The substrate cleaning method is described elsewhere . For the single layers of Sb 2 Te 3 and GeTe, first, a “seed” layer of 200 pulses (∼3 nm) film was grown at RT, followed by heating to 210 °C with a heating rate of 10 °C min –1 .…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding targets were obtained from KTECH with a purity of 99.999%. The substrate cleaning method is described elsewhere . For the single layers of Sb 2 Te 3 and GeTe, first, a “seed” layer of 200 pulses (∼3 nm) film was grown at RT, followed by heating to 210 °C with a heating rate of 10 °C min –1 .…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14] For all these applications, it is important to understand the GeTe growth mechanisms. Several studies have shown and studied the possibility to grow high quality epitaxial GeTe using either molecular beam epitaxy or pulsed laser deposition techniques, enabling to grow ultrathin (down to 1 nm) epilayers for ferroelectricity applications 15,16 or strain engineering 17 for example. However, most studies that seek to investigate GeTe focus on the crystallization of an amorphous homogeneous stoichiometric, or near-stoichiometric, thin film.…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors of strain engineering, the one with a high priority is how strain relaxes and behaves in thin films, which significantly affects the strain state of thin films. According to the bond hierarchy, the strain relaxation falls into two main strategies . (i) The strain gradually decays with the increase of film thickness, forming a strain gradient inside the thin film.…”
Section: Introductionmentioning
confidence: 99%